1990
DOI: 10.1177/107110079001100303
|View full text |Cite
|
Sign up to set email alerts
|

Shoes for the Insensitive Foot: The Effect of a “Rocker Bottom” Shoe Modification on Plantar Pressure Distribution

Abstract: The purpose of this study was to examine the effects on plantar pressure of the rocker bottom shoe, which is a frequently used intervention for the ulcerated diabetic foot. In-shoe pressure distribution was recorded during walking in a conventional extra-depth shoe which was then modified into a rocker bottom configuration with a 24 degrees rocker, and the experiment was repeated. Peak pressures in the rocker shoe were reduce by approximately 30% compared to the conventional shoe in the medial and central fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
3
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(77 citation statements)
references
References 14 publications
7
65
3
2
Order By: Relevance
“…These may reduce the risk of ulceration by reducing peak plantar pressures (Schaff and Cavanagh 1990). In the design of orthopaedic shoes for the diabetic, an indication of the plantar pressure distribution needs to be obtained, so that an insole can be designed to reduce pressure in regions prone to ulceration.…”
Section: Methods Of Prevention and Treatment Of Diabetic Foot Complicmentioning
confidence: 99%
“…These may reduce the risk of ulceration by reducing peak plantar pressures (Schaff and Cavanagh 1990). In the design of orthopaedic shoes for the diabetic, an indication of the plantar pressure distribution needs to be obtained, so that an insole can be designed to reduce pressure in regions prone to ulceration.…”
Section: Methods Of Prevention and Treatment Of Diabetic Foot Complicmentioning
confidence: 99%
“…Schaff (Schaff, et al, 1990) found changes in forefoot peak pressures with a lateral shifting of high pressure areas. Significant changes were also seen in temporal parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Specific shoe design is based on pressure measurements from a floor-reaction imprint; our group has previously demonstrated the effectiveness of this design in relieving midfoot pressures without exacerbating hindfoot or forefoot pressures (Brown, et al, 2004). Other investigations of plantar pressure changes secondary to such modified footwear are widely reported in the literature (Chesnin, et al, 2000;van Schie, et al, 2000;Fuller, et al, 2001;VanZant, et al, 2001), but investigations of changes in joint motion (kinematics) and joint loading (kinetics) are less common (Peterson, et al, 1985;Schaff, et al, 1990;Mueller, et al, 1995;Dingwell, et al, 1999;Xu, et al, 1999). The studies that do exist are generally limited to observational or quantitative two-dimensional analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent assessment of risk factors (neuropathy, foot deformity, history of ulceration and angiopathy) is necessary for the early detection of patients at risk for developing foot disease and for preventing amputation. Better patient education about foot care and appropriate footwear are expected to prevent at least half of the amputations for diabetic foot disease (Assal et al, 1985;Edmonds et al, 1986;Schaff and Cavanagh, 1990;Barth et al, 1991;Thomson et al, 1991).…”
Section: Introductionmentioning
confidence: 99%